Epidemiology of forearm fractures in the population of children and adolescents current data from Podlaskie voivodeship, Poland - Cukierman, Bartosz; Gołaszewka, Kinga; Matuszczak, Ewa; Guszczyn, Tomasz; Frankowski, Paweł; Maksimowicz, Michał; Kwiatkowski, Michał; Kwiatkowska, Ewelina; Komarowska, Marta (Journal of Education, Health and Sport, 2018)
Background: Bone fractures in children and adolescents are one of the most common reasons of the orthopedic visits in Poland. Therefore, they are an essential economical and clinical problem in that population. The most frequent is forearm fracture which comprises more than 1/3 of occurring all fractures. In this work we would like to evaluate the epidemiology of these musculoskeletal injuries in group of young people (aged 0 to 18) in Bialystok and entire Podlaskie voivodeship, focusing specifically on the anatomical location of forearm. Methods: The study included population of children and adolescents at the age of 0 to 18 years old from Bialystok city and the entire Podlaskie voivodeship, based on medical records from Paediatric Clinical Hospital in Białystok. This work included period from 1st February 2016 to 31st November 2018. The analysis of the incidence we based on 7 groups of anatomical location of fracture of forearm. Results: The work recorded 1.806 new cases of isolated fractures of the forearm in patients up to the age of 18 years. The frequency of occurrence was 0,76/1000/year in general population and 4,38/1000/year in pre-working age population. Higher frequency of fractures has been observed among boys 63,1% whereas in girls only 36,9%. The average age of a child with forearm fracture was 9,74 y.o. The proportions of fractures depending on seasonality showed that the largest number of fractures occurred in the summer (39,9%) and successively: autumn (26,87%), spring (21,88%), winter (11,37%). The most common anatomical location of forearm fracture was the distal radius metaphysis which constituted 47,34% of all fractures and the rarest was isolated fracture of the ulna shaft (1,33%). Conclusions: Authors usuly focus in their work exclusively on the fractures of the distal epiphysis of the forearm. We have evaluated all the fractures of the forearm. In the the published data, there are no clearly documented reasons or etiopathogenetic conections with bone fragility in the first two decades of life. Further studies are needed to determine the exact causes and possibilities of their elimination or reduction as well as the minimization of consequences.